2013
DOI: 10.1109/tcomm.2013.053013.130099
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Detector Randomization for Multiuser Communications Systems

Abstract: Abstract-Optimal detector randomization is studied for the downlink of a multiuser communications system, in which users can perform time-sharing among multiple detectors. A formulation is provided to obtain optimal signal amplitudes, detectors, and detector randomization factors. It is shown that the solution of this joint optimization problem can be calculated in two steps, resulting in significant reduction in computational complexity. It is proved that the optimal solution is achieved via randomization amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…The expression in (8) corresponds to the average number of symbols that are correctly received during the communication interval of length λ i T . Extending (8) to all the channels yields the average number of correctly received symbols during an interval of T seconds over all channels:…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression in (8) corresponds to the average number of symbols that are correctly received during the communication interval of length λ i T . Extending (8) to all the channels yields the average number of correctly received symbols during an interval of T seconds over all channels:…”
Section: Remarkmentioning
confidence: 99%
“…Time sharing (randomization) has attracted a significant deal of interest in the literature due to its capability to provide performance improvements for communication systems [1][2][3][4][5][6][7][8][9][10][11]. In [2], it is demonstrated that the average probability of error over additive noise channels with arbitrary noise probability density functions (PDFs) can be reduced via optimal stochastic signaling, which performs time sharing among at most three different signal levels for each information symbol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the capacity, other metrics such as probability of error, probability of detection, and outage probability are considered in various resource allocation problems; e.g., [7]- [15]. For example, in the detector randomization problem, the aim is to minimize the average probability of error of a communication system by optimizing time sharing factors and transmit power (signal) levels corresponding to different detectors at the receiver [7]- [9]. Also, a jammer can maximize the average probability of error or minimize the detection probability of a victim receiver by performing optimal time sharing among multiple power levels [12]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is obtained that the joint optimization of the transmitted signals and the detectors at the receiver leads to time sharing between at most two MAP detectors corresponding to two deterministic signal constellations. In [13], the benefits of time sharing among multiple detectors are investigated for the downlink of a multiuser communication system and the optimal time sharing strategy is characterized.…”
mentioning
confidence: 99%